Antibacterial activity test of solid soap with torch ginger's (Etlingera elatior (Jack) R.M.sm.) flower extract - Melia Sari; Mayang Sari; Cut Nurul Aswi (Universitas PGRI Semarang, 2022)
Ethanol extract of torch ginger’s flower (Etlingera elatior) is rich in active compounds such as flavonoids, alkaloids, and saponins, steroids. Flavonoids are bioactive compounds that serve as antioxidants and antibacterials. This study aims to find the antibacterial activity of solid soap with torch ginger’s flower extract against S. aureus and P. aeruginosa. This study includes the preparation of simplicia, extracts, moisture content, total ash levels, insoluble acid ash levels, water soluble extract levels. The first evaluation includes organoleptic test, pH, irritation, and stability. The formulation of the tested soap preparations was 5%, 7.5%, 10%. The data analysis was performed with ANOVA. The results of this study revealed that its ethanolic extract had a moderate category of bacterial resistance against S.aureus where in FI (5%) has a clear zone with 7 mm in diameter, FII (7.5%) 8.3 mm and FIII (10%) 10.4 mm.Furthermore,for P.aeruginosa, it has a moderate clear zone with diameter in FI (5%) is 8.86 mm, FII (7.5%) is 9.73 mm, and FIII is 10.6 mm. Torch ginger’s flower ethanolic extract had anantibacterial activity against S.aureus and P.aeruginosa with the widestclear zone is in the FIII (10%, v/v) in the number of 10.4 mm against S.aureus and 10.6 mm against P.aeruginosa with moderate resistance category.